Memoria Gottes zwischen Kontinuität und Neuschöpfung - Stoppel, Hendrik (Zeitschrift für Theologie und Kirche, 2024)
There is almost a consensus that the idea of an immortal soul is no longer appropriate and that the holistic death of the human being is a necessary part of our thinking. At the same time, the importance of the continuity of an individual's personal existence beyond their death and not just in the 'mere' memory of God cannot be denied. The text attempts, with thoughts from Paul Ricoeur and Hans Blumenberg, to show precisely the creative memoria of God as a decisive factor in the existence of a person from their eschatological re‑creation.